Research on the Impact of Rural Population Structure Changes on the Net Carbon Sink of Agricultural Production-Take Huan County in the Loess Hilly Region of China as an Example - Ma, Libang; Zhang, Wenbo; Wu, Shanshan; Shi, Zhihao (Frontiers in Environmental Science, 2022)
People are the fundamental purpose and driving force of agricultural development. The changes in population structure can directly affect social and economic development of rural areas and the entire process of agricultural production. This paper takes Huan County in the Loess Hilly Region of China as the evaluation object, the townships as the evaluation unit, the change of rural population structure as the key point, and the agricultural production as the mediating factor, to study the mechanism of agricultural net carbon sinks. The results show: 1) From 2009 to 2018, the number of rural labor force in Huan County was seriously lost, the quality of the labor force was steadily improved, and the age of the labor force was increased. The number of agricultural employees dropped from 72.6 to 49.4%. The number of people with high school education or above increased from 9.7 to 15.1%. Those over working age who participated in the labor force rose from 5.2 to 8.3%. 2) The Loess Hilly Region in the northwest of Huan County was “grain-trending,” and the River Valley and Plain Area in the southeast was “grain-removing.” The input structure index both increased first and then decreased. and the Loess Hilly Region was more dependent on the fertilizer. 3) The rural population structure affects the agricultural net carbon sink by affecting the planting structure index and the input structure index. The rural population quantity and quality structure have a significant positive effect on the agricultural net carbon sink, while the population age structure has a significant negative effect on the agricultural net carbon sink. 4) From the mediating effect, the loss of population can cause fluctuations in the agricultural net carbon sink. The improvement of population quality will promote the growth of the agricultural net carbon sink, and the aging of the population will cause the decline of the agricultural net carbon sink. 5) The return of the labor force, the improvement of labor force quality, the improvement of production methods, technological innovation, and skill training are the main ways to increase agricultural net carbon sinks and reduce emissions. This paper can lay a solid foundation for realizing the overall emission reduction target of agricultural production in the Loess Hilly Region.